2022
DOI: 10.3389/fnint.2022.797391
|View full text |Cite
|
Sign up to set email alerts
|

The “Primitive Brain Dysfunction” Theory of Autism: The Superior Colliculus Role

Abstract: A better understanding of the pathogenesis of autism will help clarify our conception of the complexity of normal brain development. The crucial deficit may lie in the postnatal changes that vision produces in the brainstem nuclei during early life. The superior colliculus is the primary brainstem visual center. Although difficult to examine in humans with present techniques, it is known to support behaviors essential for every vertebrate to survive, such as the ability to pay attention to relevant stimuli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 241 publications
(327 reference statements)
1
12
0
Order By: Relevance
“…Most importantly, Scn2a +/mice showed impaired neurophysiological and behavioral phenotypes, both due to anomalous signaling from V1 to SC. This highlights a crucial role of the top-down corticotectal pathway in forming perceptual associations to recognize and properly react to visual contexts (Tang and Higley, 2020), and a possible relationship between ASD and dysfunctions of V1 L5 projection neurons (Marco et al, 2011;Johnson et al, 2016;Jure, 2022). SC neurons represent expectations on environmental volatility in WT mice, while those on outcomes in Scn2a +/mice Thus far we have analyzed the overall activity level of SC populations during the implicit visual learning task, and demonstrated that their dynamics were largely consistent with the behavior of the posterior predictability from the Bayesian inference viewpoint (Figs.…”
Section: Chemogenetically Inhibiting Corticotectal Projection Abolish...mentioning
confidence: 96%
See 3 more Smart Citations
“…Most importantly, Scn2a +/mice showed impaired neurophysiological and behavioral phenotypes, both due to anomalous signaling from V1 to SC. This highlights a crucial role of the top-down corticotectal pathway in forming perceptual associations to recognize and properly react to visual contexts (Tang and Higley, 2020), and a possible relationship between ASD and dysfunctions of V1 L5 projection neurons (Marco et al, 2011;Johnson et al, 2016;Jure, 2022). SC neurons represent expectations on environmental volatility in WT mice, while those on outcomes in Scn2a +/mice Thus far we have analyzed the overall activity level of SC populations during the implicit visual learning task, and demonstrated that their dynamics were largely consistent with the behavior of the posterior predictability from the Bayesian inference viewpoint (Figs.…”
Section: Chemogenetically Inhibiting Corticotectal Projection Abolish...mentioning
confidence: 96%
“…The involvement of SC in these processes highlights its relevance to the neurophysiological mechanisms underlying ASD (Jure, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retinocollicular pathway, as part of the visual system, is extremely sensitive to oxygen deprivation (Wong-Riley, 2010). Lesions of this pathway lead to navigation, orientation, and visual attention deficits, and also could be involved in several neurological and psychiatric disorders such as attention deficit hyperactivity disorder, and autism (Brace et al, 2015;Mathis et al, 2015;Jure, 2022). In our research, we focus on the very early hypoxia-induced processes and their mechanisms as potential therapeutic targets serving to prevent lesions of the retinocollicular visual transmission.…”
Section: Introductionmentioning
confidence: 99%